PENERAPAN FUNGSI – FUNGSI MANAJEMEN DALAM PENGELOLAAN KELOMPOK TANI PADA PERTANIAN ORGANIK - Janiah Hermawati; Ilham Safar; Sri Adrianti Muin (Universitas Ichsan Sidenreng Rappang, 2026)
This study aims to analyze the implementation of management functions, including planning, organizing, actuating, and controlling (POAC), in the management of the Sinar Karya Farmer Group’s organic farming activities, as well as to identify the supporting and inhibiting factors affecting their implementation. This study employed a qualitative research method with a descriptive approach. Data were collected through observation, interviews, documentation, and literature review. The findings indicate that the management functions have been implemented through activity planning, organizational structuring, the implementation of organic farming practices, and the monitoring and evaluation of group activities. However, their implementation has not yet been optimal, particularly in terms of administration, documentation, member participation, and compliance with standard operating procedures (SOPs) for organic farming. Supporting factors include support from the local government, assistance from Penyuluh Pertanian Lapangan (PPL) and Pengendali Organisme Pengganggu Tumbuhan (POPT), active member participation, increased agricultural productivity, the utilization of local resources, and the strengthening of farmer group institutions. Meanwhile, the inhibiting factors include the limited capacity of farmers’ human resources, weak group administration, low participation among some members, dependence on the group leader, limited understanding of organic farming SOPs, pest and disease attacks, and limited market access for organic agricultural products.